Flowchart of study procedures. - Melinda Xu (22676384) (2025)
Background Spirituality is vital to holistic patient care and should be proactively addressed by healthcare providers as unmet spiritual needs are a major source of suffering for patients living with chronic illnesses. However, spiritual concerns are seldom referenced by clinicians during disease-related treatment discussions, particularly for minority and under-resourced patients. This paper outlines a protocol for administering and evaluating a culturally-responsive spiritual care intervention conducted with chronically ill African Americans receiving care at a community safety net health service. Methods A total of 60 African American patients who have chronic conditions and are aged 50 or older will be recruited for this study and randomly assigned to either the intervention (spiritual care program delivered by a board-certified chaplain) or the control group. All participants will complete a baseline interview that encompasses demographic information, religiosity, spiritual well-being, quality of life, and perception of care. Follow-up surveys will be conducted 12 weeks post-baseline, and participants assigned to the intervention group will also undergo a semi-structured acceptability and feasibility interview. Effect size measures and bivariate tests will be used to compare pre- and post-test outcomes while the interviews will be analyzed using constant comparative and thematic analysis. Discussion Study findings will assess the feasibility and effectiveness of a culturally-responsive spiritual care intervention for under-resourced African American patients with chronic illnesses. Furthermore, the provision of spiritual care may help patients clarify their healthcare values and decision making priorities.